Implied volatility and warrant issuing strategies: Some evidence from the Johannesburg Stock Exchange - T. T. Koorts; E. V.D.M. Smit (South African Journal of Business Management, 2002)
Financial institutions have extended their competitive realm through issuing warrants as retail products. By comparing products from different financial institutions which are similar in all respects, but are differently priced through different implied volatilities, market inefficiencies are demonstrated. Competition between Issuers lead to clearly identifiable market strategies. It is further argued that Issuers, by providing less than complete market information, have developed a position of relative strength, compared to the buyers of warrants.
Keywords: 650